1997
DOI: 10.1677/joe.0.1540241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of melatonin and oestradiol on the opioidergic regulation of LH and prolactin release in pony mares

Abstract: The aim of this study was to investigate the influence of oestradiol, melatonin and season on the opioid regulation of LH and prolactin release. Effects of the opioid antagonist naloxone (0.5 mg/kg) on LH and prolactin secretion were determined in ovariectomized pony mares. In experiment 1, mares in January (n = 6) were pretreated with oestradiol benzoate (5 micrograms/kg) for 20 days. In experiment 2, beginning in May, mares (n = 7) received melatonin (15 mg) for 15 days and subsequently a combination of mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Naloxone-inducible PRL release does not exist in intact, non-pregnant mares but can be activated by oestradiol-progesterone and melatonin treatment in ovariectomised mares (Aurich et al 1994(Aurich et al , 1997. Thus, pregnancy is the only reproductive state in which opioids inhibit PRL secretion in non-pretreated mares.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naloxone-inducible PRL release does not exist in intact, non-pregnant mares but can be activated by oestradiol-progesterone and melatonin treatment in ovariectomised mares (Aurich et al 1994(Aurich et al , 1997. Thus, pregnancy is the only reproductive state in which opioids inhibit PRL secretion in non-pretreated mares.…”
Section: Discussionmentioning
confidence: 99%
“…In cyclic mares, the opioidergic inhibition of LH secretion is activated by a sequence of oestrogen and progesterone influence characteristic of the oestrous cycle. In seasonal anoestrous mares, the opioidergic inhibition of LH release can be stimulated by a prolonged period of oestrogen exposure or independently of ovarian factors (Aurich et al 1994(Aurich et al , 1995(Aurich et al , 1997. Opioids inhibit PRL secretion in steroid-treated (Aurich et al 1995) and melatonin-treated (Aurich et al 1997) ovariectomised mares but not in non-pregnant, ovaryintact mares.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997 [79], they reported that naloxone, an opioid antagonist agent, stimulated prolactin secretion in mares that had previously been administered melatonin but not in mares that had received estradiol or melatonin plus estradiol. Naloxone administration to otherwise untreated mares in the breeding and nonbreeding season had no effect on prolactin secretion [80].…”
Section: Opioid Involvementmentioning
confidence: 99%
“…Aurich et al (1995b) reported that prolactin secretion was induced by naloxone treatment in ovariectomized pony mares that had been pretreated with estradiol benzoate. However, Aurich et al (1997) reported that prolactin release was significantly increased by naloxone administration in ovariectomized pony mares after mares had been pretreated with only melatonin, but not when they received a combination of estradiol benzoate and melatonin. Thus, the literature is contradictory on the effects of opioid antagonists on prolactin secretion in horses.…”
Section: Discussionmentioning
confidence: 99%